Spatiotemporal variability and diffusive emissions of greenhouse gas in a shallow eutrophic lake in Inner Mongolia, China. (December 2022) - Li, Guohua; Zhang, Sheng; Shi, Xiaohong; Zhan, Liyang; Zhao, Shengnan; Sun, Biao; Liu, Yu; Tian, Zhiqiang; Li, Zhijun; Arvola, Lauri; Uusheimo, Sari; Tulonen, Tiina; et al.
Graphical abstract: Highlights: Greenhouse gases emissions from a shallow lake in semi-arid area were estimated. Considerable spatiotemporal variation in dissolved CO2, CH4, and N2 O concentrations. Spatial variability of GHG was associated with lake bathymetry and abundance of macrophytes. CH4 contributed 83% to the total emissions as CO2 -equivalents. Lakes are an important source of carbon to the atmosphere. Abstract: Aquatic ecosystems are globally significant sources of greenhouse gases (GHG) to the atmosphere, offsetting the terrestrial sinks. A one-year field study was carried out in a shallow eutrophic Lake Wuliangsuhai, Inner Mongolia (draining waters from one of the largest irrigation areas in China), to estimate diffusive GHG fluxes and their relative importance in global warming potential (GWP). Our results showed high spatiotemporal variation in dissolved CO2, CH4 and N2 O concentrations, while they did not differ significantly between the bottom and surface layers of the shallow waterbody. In general, GHG concentrations and diffusive fluxes were higher in the north part of the lake than in the south. GHG concentrations in the water under the ice were significantly higher than those during the open-water period. Spatial variability of GHG concentrations varied with the bathymetry of the lake. The location of study sites relative to the main inflow and abundance of submerged macrophytes were the main controlling factors of GHG concentrations, as indicated by the consistency of GHG concentrations at the sampling sites, particularly for N2 O. The total diffusive GHG emission from Lake Wuliangsuhai was 76.9 ± 5.4 Gg CO2 equivalents yr −1, with CO2, CH4 and N2 O contributing 16 %, 83 %, and 1 %, respectively. Overall, the results suggest that shallow lakes in mid-latitude arid areas with cold winters can be potentially important GHG sources. However, those lakes are insufficiently represented in the scientific literature, and therefore they deserve more research attention.